MUTUALISM IN LESSON STUDY - Patang Hafira (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2018)
Lesson study has commonly three stages in the implementation. They are plan, do, and see. In the process, a relationship occurs between people who are involved in it. They are the teachers, students, and observers. This research focuses about the positive relation happened between teachers and observers. Positive relation between people who are involved in learning process could improve classroom quality. The positive relation is named mutualism. In biological term, mutualism is when two organisms of different species "work together", each benefiting from the relationship. Meaning contained in the term is used by the researcher to indicate a relationship that occurs in the lesson study process. This research aims at finding out the mutualism in lesson study, especially the mutualism between teachers and students. The method used in this research was qualitative method. The research took place at English Education Study Program, Cokroaminoto Palopo University, South Sulawesi, Indonesia. Teachers and students in this institution were taken as the participants of the research. Data gained through classroom observation and focus group interview. The result of the research shows that mutualism happens between teachers and observers.